Perlindungan Hukum Kepailitan Perusahaan Solvable di Indonesia - Devi Andani (Kajian Hukum, 2022)
Abstract This study aims to determine the legal protection for bankruptcy of solvable companies in Indonesia. The method used is qualitative by following the typology of normative legal research, data is collected by means of literature studies and documents written descriptively and analyzed qualitatively. The results of this study indicate that bankruptcy decisions can occur in solvable companies, if the party applying for a bankruptcy statement has fulfilled the requirements, namely, there are debtors, there are two or more creditors, there is debt, and at least one debt has fallen due and can be paid off. billed. Meanwhile, legal protection for solvable companies that are declared bankrupt is not regulated in Law Number 37 of 2004. According to this law, if the company has been declared bankrupt, then the company is no longer capable of carrying out legal actions and general confiscation is carried out on all company assets even though the company is concerned are included in solvable companies. In the future, the Indonesian Bankruptcy Law must be designed to protect solvable companies by providing arrangements regarding company reorganization as a way to save companies from bankruptcy, providing more detailed requirements so that certain parties can apply for bankruptcy statements, and providing legal protection for solvable companies against bankruptcy. bankruptcy threat.